The Effect Of Play-Way Teaching Strategy On Primary School Pupils’ Acquisition Of Basic Science Concepts - Victoria Ihekerenma, Iroegbu (Advances in Social Sciences Research Journal, 2017)
This study investigated the effect of play-way teaching strategy on primary school pupils’ acquisition of science concepts in the basic science and technology curriculum. The sample for the study consisted of sixty boys and girls in equal proportion that was randomized into three treatment groups. Stratified sampling technique was used in selecting equal number of boys and girls into the three groups. The treatment groups were free play group, teacher mediated play group and direct instruction groups with vicarious play activities. The treatment lasted three weeks for the groups who were pupils that successfully completed primary three at the end of the session. The content centered on basic ideas on water, floating and sinking, measures, simple machines and motion. A twenty item multiple choice objective test with reliability of 0.79 was used to determine learning outcomes. T-test analysis of group mean scores was used to evaluate the two hypotheses. Teacher structured play-way group obtained a mean score of 12.9 while direct instruction group obtained a mean score of 10.0. The obtained t-value of 4.061 is significant at p < .05. There was no gender effect among play-way pupils as boy and girls achieved mean scores of 12.1 and 12.2 respectively. The obtained t-value of 0.137 was not significant at five percent probability.